Language and ideology. - Dirven, René; Frank, Roslyn; Ilie, Cornelia (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2001)
Together with its sister volume on Theoretical Cognitive Approaches, this volume explores the contribution which cognitive linguistics can make to the identification and analysis of overt and hidden ideologies. This volume shows that descriptive tools which cognitive linguistics developed for the analysis of language-in-use are highly efficient for the analysis of ideologies as well. Amongst them are the concept of grounding and the speaker's deictic centre, iconographic reference, frames, cultural cognitive models as a subgroup of Idealized Cognitive Models, conceptual metaphors, root metapho.